The beauty quotient formula how to find your own beauty quotient to look your best- no matter what your age - Robert M Tornambe; Karen Moline (Carlsbad, Calif. : Hay House, 2010)
"During his 25-year career as a plastic surgeon, Dr. Robert M. Tornambe has worked with thousands of women and spent countless hours contemplating the nature of beauty—particularly in situations where he was asked to perform a procedure he believed would diminish his patient’s natural good looks. In an attempt to provide as many options as possible, he focused on helping women understand that while surgery has its